Illustrating and Designing Quranic Imagery - Almenoar, Lubna (Journal of the American Academy of Special Education Professionals, 2009)
Selected verses from Abdullah Yusuf Ali’s English language translation of the meaning of the Quran have been used as a literary text to teach both descriptive and figurative imagery (including similes, metaphors and symbols) to students at the undergraduate level in an Islamic institution. The technique--Illustrating and Designing for teaching imagery has been selected to accommodate the text. The group of students was taught imagery using one technique covering 2 class sessions. Assignments were given to derive data for the evaluation of the level of understanding of the lessons on imagery. An analysis of the data from the assignments shows a high level of understanding of the lessons on imagery by the students.